2013
DOI: 10.1007/s11999-013-2988-5
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Sponges for Local Synergistic Infection Therapy: A Pilot Study

Abstract: Background Although bacterial antibiotic resistance is increasing, fewer new antibiotics are being developed to compensate. Localized delivery of synergistic antiseptics and antibiotics with a chitosan sponge device may offer an alternative infection treatment. Questions/purposes In this pilot study, we asked whether antiseptic and antibiotic combinations provided in vitro synergism against Staphylococcus aureus, whether synergism reduces cell viability, and whether their combination releases drugs at inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…43 Noel et al 44 and Smith et al 45 suggested the possibility of using a CS sponge device as an alternative to deliver antibiotics locally as an adjunctive therapy for the treatment and prevention of infections, from open traumatic wounds to prophylactic use in surgical sites. Furthermore, a CS sponge can be used as a drug reservoir 43 or a storage form for CS systems.…”
Section: Morphological Characteristics Of Ace-np and Spongesmentioning
confidence: 99%
“…43 Noel et al 44 and Smith et al 45 suggested the possibility of using a CS sponge device as an alternative to deliver antibiotics locally as an adjunctive therapy for the treatment and prevention of infections, from open traumatic wounds to prophylactic use in surgical sites. Furthermore, a CS sponge can be used as a drug reservoir 43 or a storage form for CS systems.…”
Section: Morphological Characteristics Of Ace-np and Spongesmentioning
confidence: 99%
“…15,18,19 Chitopharm S chitosan was purchased from Chitinor AS (Tromsoe, Norway) with 82.5 6 1.7 degree of deacetylation (DDA), 251 6 17 kDa weight-average molecular weight (MW) and 2.013 6 0.145 polydispersity index. All acids and buffer solutions were obtained from Fisher Scientific (Pittsburg, PA).…”
Section: Fabricationmentioning
confidence: 99%
“…Localized antimicrobial drug delivery systems, including biomaterial carrier matrices and coatings on implants, have become a focus to combat biofilm formation and infection for both preventive and treatment strategies [1,7,13,27,29,43,49,63,64]. We provide the initial description of a novel lipid-based material we have developed to serve as a carrier matrix for antibiotics that can be applied to an implant with clinician-selected antibiotics at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…The primary strategy for prevention is aseptic surgical technique followed by prophylactic systemic administration of antibiotics [28,71]. Antiinfective biomaterials are increasingly used as an adjunctive strategy to prevent implanted biomaterial infections and to inhibit biofilm-forming microorganisms [13,27,44,49,55,63,64]. Commonly used local antibiotic delivery systems range from antibiotic-loaded bone cement to calcium-based drug delivery systems to sprinkling antibiotics within the wound site [8,24,40,42].…”
Section: Introductionmentioning
confidence: 99%